The role of E2F1 in promoting EIF4EBP1 transcription in cryptorchid mice: association with autophagy in germ cells - Zhang, Jianguo; Liu, Yanhui; Zhang, Hailong; Yang, Lin; Sun, Danjing; Xiao, Lili; Wang, Xiaoyun; Wu, Xiangming (Frontiers in Genetics, 2025)
IntroductionCryptorchidism can cause excessive germ cell autophagy and apoptosis to impair fertility. This study investigates the role of E2F1 in regulating EIF4EBP1 expression and its contribution to excessive autophagy and apoptosis in cryptorchidism.MethodsA cryptorchidism mouse model was established through surgical intervention, while an in vitro cryptorchid spermatogonial cell model was created using heat stress. Expression levels of EIF4EBP1 and key proteins involved in autophagy and apoptosis were assessed by reverse transcription quantitative polymerase chain reaction (RT-qPCR) and Western blotting Testicular damage and fibrosis were evaluated through HE staining and Masson staining. Serum and testicular testosterone levels were measured, alongside markers of oxidative stress. The regulatory role of E2F1 on EIF4EBP1 was confirmed by dual-luciferase reporter assays and ChIP. Further analysis of the effects of E2F1 and EIF4EBP1 on testicular damage, apoptosis, and autophagy was performed by manipulating EIF4EBP1 expression.ResultsIn the cryptorchidism mouse model, reduced testicular volume and weight, increased testicular damage and fibrosis, decreased testosterone levels, and impaired sperm count and vitality were observed. In the in vitro cryptorchid spermatogonial cell model, cell viability was reduced, while oxidative stress was elevated. Both autophagy and apoptosis were exacerbated in these models. EIF4EBP1 expression was upregulated, and its knockdown ameliorated the adverse effects. E2F1 was identified as an upstream regulator of EIF4EBP1, with knockdown of E2F1 significantly decreasing EIF4EBP1 promoter activity and binding. Inhibition of E2F1 using HLM006474 reduced EIF4EBP1 expression, while EIF4EBP1 overexpression aggravated autophagy and apoptosis.ConclusionE2F1 regulates EIF4EBP1 expression in cryptorchidism, contributing to excessive autophagy and apoptosis. Inhibiting E2F1 reduces these pathological processes, alleviating testicular damage and improving fertility, highlighting potential therapeutic targets for cryptorchidism.